Partisipasi politik perempuan dalam kiprah dakwah partai keadilan sejahtera - Khadijah, Siti (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The purpose of this study is to analyze PKS's strategy to build women's political participation in its da'wah activities. The crisis of democracy is rationally caused by the lack of formal participation of the community, especially women in national politics. PKS has not maximized in utilizing alternative forms of women's participation through social media to fulfill affirmative policies. The efforts made by PKS have not been maximized in utilizing the strong influence of the media effects of the 4.0 era to increase women's political participation. The theoretical reference used is the theory proposed by Aeron Davis